2007
DOI: 10.1021/ac0700272
|View full text |Cite
|
Sign up to set email alerts
|

Using Statistical Models To Identify Factors That Have a Role in Defining the Abundance of Ions Produced by Tandem MS

Abstract: A database of 5448 peptide tandem mass spectra acquired in a quadrupole time-of-flight mass spectrometer was generated for peptides derived from proteins digested with trypsin. Peptides were identified from their mass spectra by the Mascot algorithm. Statistical models were then used to investigate factors influencing the abundance of ions formed. Separate models were formulated for b and y ions as it was thought that different factors may influence the formation of each type of ion. Several factors were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
35
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…The lower the peptide charge and the lower the ion charge the higher the ion intensity which is also reported by one of the previous studies that charge state can have a dramatic effect on fragmentation of peptide [3]. B ions had significant lower intensity than the y ions (Table II), as most authors reported that y ion-series is usually more intense then b ion-series [2,3,4]. Thus, ions from non-mobile peptides, highly charged ions from highly charged peptides and b ions may not surpass the detection threshold and may not be used for accurate peptide identification.…”
Section: IIIsupporting
confidence: 72%
See 2 more Smart Citations
“…The lower the peptide charge and the lower the ion charge the higher the ion intensity which is also reported by one of the previous studies that charge state can have a dramatic effect on fragmentation of peptide [3]. B ions had significant lower intensity than the y ions (Table II), as most authors reported that y ion-series is usually more intense then b ion-series [2,3,4]. Thus, ions from non-mobile peptides, highly charged ions from highly charged peptides and b ions may not surpass the detection threshold and may not be used for accurate peptide identification.…”
Section: IIIsupporting
confidence: 72%
“…The accuracy of the algorithms to identify peptides based on matches of the mass spectra observed to that expected based on known peptide sequence peaks is directly dependent on the precision of the spectra peaks. The fragmentation of peptide in MS/MS is a complex process and influenced by number of factors [2]. Peak intensity varies within and across ions within a peptide and the ions that do not surpass a minimum peak threshold may not be detected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is still some debate on the structures of b-ions [7], the lowenergy fragmentation reactions of protonated peptides that result in the formation of both sequence and non-sequence ions are fairly well understood and have been the subject of several reviews [5][6][7][8][9][10][11]. This is due to the world-wide research efforts of many groups who have either conducted experimental and theoretical studies on small model peptides [5][6][7][8][9][10] or used statistical methods to interrogate large, curated libraries of MS/MS spectra of "real world" peptides, typically formed via tryptic digestion of proteins [12][13][14][15][16][17][18][19][20][21][22]. While more refined fragmentation models such as Paizs and Suhai's "pathways in competition (PIC)" have been developed [10], the "mobile proton" has remained center stage.…”
mentioning
confidence: 99%
“…Peptide fragmentation trends derived from large collections of spectra have been published by several groups, for example [6][7][8][9][10][11], and recently reviewed [12]. Most of these studies examined the effect of specific residues, especially those adjacent to the breaking bond, and their relation to "proton mobility", on the extent of formation of specific fragments, mainly y and b ions.…”
mentioning
confidence: 99%